To Study Consumers’ Use of Information on Food Labels in Vietnam - Ha, Nguyen Minh; Dung, Nguyen Thi (International Review of Management and Marketing, 2017)
The information on food labels is an important source to guide consumers in making choices of food. The objective of this study is to analyze factors affecting consumers’ awareness of food labeling information. The survey was conducted among 375 people with age of above 18 year old in Vietnam. Using the method of descriptive statistical analysis, testing the reliability of scale (Cronbach’s Alpha), exploratory factor analysis (EFA), and multivariate regression analysis, the results showed that there are 04 factors affecting consumers’ intention of using the information on food labels: Attitudes toward information on food labels, effect of society, perceived behavioral control, and concern about diet - health. In addition, the customers’ intention of using the information on food labels has a positive impact on their use behavior of information on food labels. Keywords: Food labels, intention, behavior, using information on food labels JEL Classifications: L66, M